Influence of message error type on Korean adults' attitudes toward an individual who uses augmentative and alternative communication. (June 2015) - Kim, Jae Ri; Kim, Young Tae; Lee, Hyun Jung; Park, Eun Hye
Abstract The aim of this study was to investigate the influence of types of message errors on the attitudes of Korean adults toward a person who uses AAC. The attitudes of 72 adults who speak native Korean were examined through attitude questionnaires completed after viewing videotaped conversations between a boy with cerebral palsy and an adult without disabilities. Each interaction video involved a message with one of six error types, including various types of syntactic, semantic, and pragmatic errors. The participants provided information on their attitude towards the person who used AAC, and ranked their preferences among the six messages. The results provide evidence that attitudes towards the individual using AAC were most positive (in comparison with other conditions) when a pragmatic error was observed. Messages containing a syntactic error were ranked most favorably. Spearman's correlation analyses revealed some relationship between attitudes rating and preferences ranking. Our results provide evidence that specific language and cultural contexts may play an important role in shaping attitudes toward those who use AAC.